Environmental and Economic Aspects of Afforestation in Ukraine in Terms of Sustainable Land ManagementEcological and economic aspects of forestry in Ukraine in the context of sustainable land using - Dudiak, N.; Pichura, V.; Potravka, L. (Land Management, Cadastre and Land Monitoring, 2019)
Over the last half a century, the total area of forests in the world has decreased significantly. Ukraine belongs to countries with low quantity of forests and deficient of woods, because the level of forest cover is 15.9% with the required optimal value of 25-30%. Steppe areas are characterized by 1.9–4.8% of forest cover. The current total area of forest land belonging to the forest fund of Ukraine is 10.4 million hectares, including 9.6 million hectares of forested vegetation, about 3.5 million hectares of forests have restrictions in forest management. In 2008–2017, 4.03 million hectares of forests were cut down in Ukraine and additionally destroyed by fire, pests, storms, and by poachers about 170.7 thousand hectares, only 16.3% of this area was recovered. In order to ensure optimal forest cover, it is necessary to differentially restore the forest area in Ukraine by 6.0–9.2 million hectares. The average field protective forest cover in some physical-geographical zones of Ukraine varies within 1.3–1.5%, the optimal should be 3.0–4.5%. In particular, about 76.0% of the territory of the steppe zone of Ukraine has insufficient forest cover, which causes systematic negative manifestations of water and wind erosion. This situation is complicated by the high level of agricultural development of the southern regions - up to 97%, which causes a low degree of environmental sustainability of landscapes to preserve soil fertility. Retrospective analysis showed a significant decrease in the area of forest protection strips over the past 60 years by 1.9–2.3 times. The total loss of protective forest strips in Ukraine over the last 10 years is 10 071 hectares, which has weakened the nature protection function of the forest plantation and caused the scale of water and wind erosion. The survey uses data from the State Statistics Service and the State Geo-cadastre of Ukraine during 2008–2017. Decryption of Earth remote sensing data and use of a series of correctly calibrated MODIS satellite images (geometric resolution 230 × 230 m) made it possible to determine the ratio of the spatial distribution of the forest fund to the agricultural land on the territory of Ukraine. Using the Zonal Statistics of Spatial Analyst Tools module, of the ArcGIS program was determined forested and plowed lands within separate administrative and territorial units. The difficult situation in Ukraine, in which the state of forest ecosystems does not meet the ecological and economic requirements, is caused by the complexity of management decisions in the field of forestry. The obtained results make it possible to substantiate the need for spatial-differential measures of forest restoration and implementation of land and water preservation measures for optimization of the land fund on the basis of adaptive-landscape principles, which allows to create preconditions for rational use and rehabilitation of forest and land resources of Ukraine.Keywords: ecological and economic aspects, forest fund, protective forest strips, forest cover, plowing, ecological sustainability, sustainable land use, Ukraine, geomodeling.